Cost-effective interventions to prevent prescription drug misuse: a systematic review - Rodríguez-Tanta, L. Yesenia; Summers, Amanda; Shaya, Fadia T. (Frontiers in Public Health, 2025)
BackgroundPrescription drug misuse (PDM), which involves the overprescription or inappropriate use of medications such as opioids, benzodiazepines, and stimulants, is one of the primary drivers of the opioid crisis. Identifying and understanding the most cost-effective interventions for preventing PDM is crucial.ObjectivesTo conduct a systematic review to identify and synthesize recent cost-effectiveness studies of interventions to prevent PDM.Search methodsWe searched MEDLINE, EMBASE, Scopus, PsycINFO, EconLit, and Tufts CEA Registry from January 2019 until June 2024 to identify cost-effectiveness or cost-utility analyses.Selection criteriaWe included comprehensive economic evaluations addressing our research PICO question.Data collection and analysisTwo reviewers independently screened and selected studies for inclusion, extracted study information, and assessed the quality of all included studies. The findings were synthesized narratively to provide a comprehensive overview.Main resultsWe identified eight recent interventions of fair to good quality that focus on addressing PDM, but none of them addressed benzodiazepines or stimulants. These interventions involved modifications in prescribing behavior, distribution of naloxone in community pharmacies, the use of medication for opioid use disorder with “treatment add-ons,” and education-based strategies. Variations in time horizons, comparison groups, and modeling assumptions led to differences in cost-effectiveness and quality-adjusted life years (QALYs). Nonetheless, all interventions were deemed cost-effective, particularly from a healthcare perspective.ConclusionEvidence suggests that while the identified interventions for preventing PDM are cost-effective, their scope remains limited. Further research is needed to address the misuse of other prescription drugs and to evaluate the cost-effectiveness of Prescription Drug Monitoring Programs (PDMPs), particularly their impact on clinicians’ prescribing practices for patients with chronic opioid use. Additionally, incorporating societal perspectives in future studies will be crucial to enhancing policy decisions and developing comprehensive strategies to combat prescription drug misuse globally.